Lattices from maximal orders into quaternion algebras - Alves, C. [UNESP]; Belfiore, J. -C. (Elsevier B.V., 2015)
We propose an algebraic framework to construct dense lattices from maximal orders of a quaternion algebra whose center is an imaginary quadratic field. This work extends [21] where a method called algebraic reduction has been proposed to efficiently decode the Golden code [14]. In particular, we propose four new constructions of E-8 lattice from left ideals of maximal orders of some quaternion algebras with centers Q(root-d), d = 1,2,3,7. (C) 2014 Elsevier B.V. All rights reserved.